2018
DOI: 10.22478/ufpb.2317-6032.2018v22n4.37491
|View full text |Cite
|
Sign up to set email alerts
|

Validade De Um Questionário De Comportamento Sedentário Em Escolares De 9 a 15 Anos De Idade

Abstract: Introdução: Existem poucos instrumentos validados para avaliar o comportamento sedentário em crianças e adolescentes brasileiros. Objetivo: Avaliar a validade de um questionário de comportamento sedentário em 117 escolares, de ambos os sexos, de 9 a 15 anos de cinco escolas públicas de Curitiba/Brasil. Métodos: O questionário avaliou o tempo gasto em atividades sedentárias durante uma semana e um final de semana típico. O tempo reportado em atividades sedentárias foi validado contra estimativas de tempo sedent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…QASA has positive indicators of validity and reproducibility in Brazilian adolescents (ICC 0.88; 95% confidence interval [95% CI] 0.82-0.91; rho: 0.79; p <0.01). 25,26 Teenagers who reported > 4 hours/day in front of a screen were considered in the category of high screen time.…”
Section: Methodsmentioning
confidence: 99%
“…QASA has positive indicators of validity and reproducibility in Brazilian adolescents (ICC 0.88; 95% confidence interval [95% CI] 0.82-0.91; rho: 0.79; p <0.01). 25,26 Teenagers who reported > 4 hours/day in front of a screen were considered in the category of high screen time.…”
Section: Methodsmentioning
confidence: 99%
“…Other studies found that girls as a risk factor 4 or did not find any relationship with high screen time. 5 Despite this inconclusive relationship, there is evidence that girls are engaged in other types of sedentary behaviors, unlike screen time (television, video games, and computer), such as educational, cultural, and other extracurricular 3,6,7,21 which might explain our results. Additionally, during adolescence, girls undergo body transformations and in proportions that can hinder motor and physiological performance, causing changes in behavior patterns.…”
Section: Discussionmentioning
confidence: 59%
“…Then, Body mass index (BMI) was calculated as weight (Kg)/height (m), and the BMI classification Status followed the reference proposed by the World Health Organization for each sex and age. 20 The Brazilian version 7,21 of the Adolescents Sedentary Activity Questionnaire (ASAQ) assessed the screen time. The ASAQ has adequate validity, and reliability (CCI=0.90, CI95%=0.86-0.93) 7 to measure sedentary activities in Brazilian adolescents.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, several studies have been developed to understand the relationship between this behavior and health outcomes 6 , identifying methods capable of reliably measuring these manifestations can help guide more assertive recommendations for populations. Some countries have developed public health guidelines that include recommendations about SB [7][8][9][10][11] . These guidelines are generally based on epidemiological studies, which evaluate SB using device-derived (accelerometry and devices that detect postural changes) and subjective methods (questionnaires) 12 .…”
Section: Introductionmentioning
confidence: 99%